Clinical and sociodemographic factors related to the timing of autism diagnosis in an Italian cohort of children - Cianfa, Alessia; Guerrera, Silvia; Fucà, Elisa; Annechini, Emma; Napoli, Valentina; Vicari, Stefano; Valeri, Giovanni (Frontiers in Psychiatry, 2025)
IntroductionThe onset of features associated with “Autism Spectrum Condition” can vary significantly in both timing and presentation. A formal diagnosis often does not align with the emergence of early signs due to challenges in recognizing the initial manifestations of neurodevelopmental differences. Current research shows limited consensus regarding clinical and sociodemographic factors linked to early versus late diagnoses, underscoring the need for further investigation.MethodsData were retrospectively collected from clinical records of children evaluated for suspected autism at the Child and Adolescent Neuropsychiatry Unit of an Italian pediatric hospital between 2016 and 2023. The standardized evaluation included neuropsychiatric examination, assessment of cognitive and adaptive functioning, evaluation of autistic traits, and a comprehensive psychopathological profile. Correlational analyses examined clinical and sociodemographic variables associated with diagnosis timing, while a linear regression model was used to identify independent predictors. Inclusion criteria included a first diagnosis of autism or high likelihood of autism, and an age between 18 and 71 months. Exclusion criteria included known genetic conditions or a prior autism diagnosis.ResultsThe final sample included 150 children (mean age: 43.71 ± 13.6 months; 123 males, 27 females). Among clinical variables, cognitive and developmental differences and parental recognition of early communication variations were linked to earlier diagnosis, while a distinct emotional-behavioral profile was associated with later diagnosis. Regarding sociodemographic factors, being a first-born child and higher parental stress were correlated with delayed diagnosis. Parental age and education showed no significant associations. Only cognitive and developmental profiles, along with early symptom recognition (ADI-D), emerged as the strongest predictors of early diagnosis. Conclusions: These results emphasize the critical need to enhance early identification of autism and to minimize the adverse effects associated with delayed diagnosis. They also underline the clinical relevance of caregiver education—particularly for first-time parents—as a strategy to facilitate timely recognition and intervention.